PELAKSANAAN EKSEKUSI JAMINAN FIDUSIA DALAM PERJANJIAN PEMBIAYAAN DI KSPS LOGAM MULIA KECAMATAN KLAMBU KABUPATEN GROBOGAN - Junaidi Abdullah (Program Studi Hukum Keluarga Islam, 2017)
Any loan or financing agreement made by a sharia financial institution, whether bank or non-bank, more particularly KSPS Logam Mulia, usually requires a guarantee. Guaranteed goods guaranteed by the community or its members may be movable objects such as motorcycles or cars (guaranteed by BPKB) and may be non-moving objects in the form of buildings or land (guaranteed usually land certificates) .To to legalize the guarantee goods, the guarantee goods. For moving objects in the form of fiduciary and immovable property through mortgages. With the existence of objects collateralized by the public or members of the Islamic financial institutions, both banks and non-banks with fiduciary guarantee will provide the legal force for the institution to execute objects that have been guaranteed if the people who borrow violate the promise or wanprestasi.But in fact, KSPS Logam Mulia has never executed forcibly to the community or its members who have neglected or are unable to perform its obligations ie paying installments on loans or financing it has received. From the results of the research can be known execution fiduciary guarantee in KSPS Logam Mulia Klambu District Grobogan District does not execute fiduciary guarantee directly against members who do not perform the obligation mengangsurnya. What factors are the background of not directly executing tehadap assurance of fiduciary objects in KSPS Logam Mulia Klambu District Grobogan Regency is: The reason shariah and Reason kinship.